Fostering Openness: Catholic-Muslim Student Encounters in Ciamis, West Java - Siswanto, Mikael Adi; Andini, Andini; Truna, Dody S. (FISIP UIN SGD Bandung, 2025)
Interfaith encounters play a vital role in fostering social harmony and mutual understanding among religious communities, especially in diverse societies. This study examines the efforts of Santo Yakobus High School in Jakarta to promote interreligious dialogue through visits to Darussalam Islamic Boarding School in Ciamis. The initiative involves Catholic and Muslim students engaging in meaningful interactions to overcome prejudice and build friendships. Recognizing the challenges posed by societal biases and misconceptions, the study highlights the importance of cultivating an attitude of openness as a foundational element for successful encounters. Using qualitative methods and an anthropological approach, the research identifies four key stages in the process of internalizing openness among Santo Yakobus students. These stages enable participants to develop insights, foster social connections, and establish interfaith friendships, offering a model for promoting peaceful coexistence and deeper understanding between religious communities. Contribution: The concept of openness is presented as essential for facilitating meaningful interactions. This framework not only addresses existing prejudices but also promotes a culture of understanding and respect between diverse religious communities.